Quantifying mammal biodiversity co‐benefits in certified tropical forests. Issue 3 (16th January 2017) - Sollmann, Rahel; Mohamed, Azlan; Niedballa, Jürgen; Bender, Johannes; Ambu, Laurentius; Lagan, Peter; Mannan, Sam; Ong, Robert C.; Langner, Andreas; Gardner, Beth; Wilting, Andreas
Abstract: Aim: Financial incentives to manage forests sustainably, such as certification or carbon storage payments, are assumed to have co‐benefits for biodiversity conservation. This claim remains little studied for rain forest mammals, which are particularly threatened, but challenging to survey. Location: Sabah, Malaysia, Borneo. Methods: We used photographic data from three commercial forest reserves to show how community occupancy modelling can be used to quantify mammalian diversity conservation co‐benefits of forest certification. These reserves had different management histories, and one was certified by the Forest Stewardship Council. Results: Many threatened species occupied larger areas in the certified reserve. Species richness, estimated per 200 × 200‐m grid cell throughout all reserves, was higher in the certified site, particularly for threatened species. The certified reserve held the highest aboveground biomass. Within reserves, aboveground biomass was not strongly correlated with patterns of mammal richness (Spearman's rho from 0.03 to 0.32); discrepancies were strongest along reserve borders. Main conclusions: Our approach provides a flexible and standardized tool to assess biodiversity and identify winners of sustainable forestry. Inferring patterns of species richness from camera‐trapping carries potential for the objective designation of high conservation value forest. Correlating species richness with aboveground biomass further allows evaluating the biodiversity co‐benefits of carbon protection. These advantages make the present approach an ideal tool to overcome the difficulties to rigorously quantify biodiversity co‐benefits of forest certification and carbon storage payments.